Factors Affecting Small-Scale Livestock Farming in Kenya - Kelio, Armion (International Journal of Livestock Policy, 2022)
Purpose: This study aims at examining the factors influencing small-scale livestock farming in Kenya. Methodology: A majority of the small-scale livestock farmers in many counties were past their youthful years, with most respondents cited at above fifty years. A sample of small-scale livestock farmers was selected, using the Proportionate Stratified Random Sampling technique. An Ordinary Least Square (OLS) multiple regression model will be used to determine the factors that affect livestock numbers in Kenya. Findings: The study found out that 56% of the farmers in some counties showed the most aggression in seeking out livestock farming related information from many other sources other than from their counterpart farmers. These farmers quest for extensive information on dairy farming was also highlighted by their expansive peer to peer networks. Unique Contribution to Theory, Policy and Practice: Counties should make more commonage land available to the small-scale livestock farmers in order to cope with the increasing population of emerging farmers. Commonage land management should be strengthened. Small-scale livestock farmers should be trained to make reserves such as hay and silage so they can conserve surplus forage in rainy seasons. Government should provide subsidies for purchase of breeding stock and dosing products. Distribution policies that will ensure that all smallholder cattle and sheep farmers at grassroots level benefit should also be put in place.